MEKANISME PENGAWASAN TITIK-TITIK REKLAME DI KAWASAN SIMPANGLIMA KOTA SEMARANG - Bayu Indra Permana; Puji Astuti; Sulistyowati . (Journal of Politic and Government Studies, 2014)
Simpanglima function as a public space in accordance with Regulation No. 14 Year 2012Article 4 Paragraph 4 ( a) that menyebutan " means the environment " is a support facility, whichserves to maintain and develop the economic, social and cultural. Billboard itself is the object,instrument, deed and or media that shape and style manifold for introducing commercialpurposes, advocate, promote, or to draw public attention to goods, services can be seen, read orenjoyed by the public. Billboards are also a source of revenue. Simpanglima violates the rules,based on the Regulation No. 8 of 2006 on the implementation of the Mayor 's Decree No.billboards and on the determination of the layout 510.1/145 billboards in the city of Semarang.This study aims to provide Simpanglima the assumption that public space should be able torealize the convenience and aesthetic installation of billboards based on existing regulations.Government through the Department of Street Lighting and Advertising Management ( PJPR )should be able to reduce the number of billboards in the area of Simpanglima, both the CityGovernment land or private land . The government should be able to push boundaries by creatinga billboard point of reference standard and are looking for other ideas for local revenues byraising taxes Simpanglima billboards in the area .And the need for supervision reklmae ketegasain Supervision by field supervision over the administration of the Department PJPR warningletter. Implementation in the field of surveillance carried out by the municipality of Semarangsuch as billboards wild / Simpanglima troubled region is not optimal. Shortage of HumanResources ( HR ) became one of the inhibiting factors in terms of supervisionKeywords: oversight mechanisms, Advertising, Simpanglima